Effect of a Living–Learning Community on Nursing Student Outcomes—A Prospective Cohort Study. - Bennett, Mary; Travelsted, Melissa; Shoumake, Vickie; Atkinson, Matthew (Nursing Reports, 2025)
Background/Objectives: Prior studies have shown that most students seeking entry into a nursing program (also known as pre-nursing students) do not make it into the nursing profession, mostly due to failing one or more science courses in their first year of college. These students give up on nursing, dropping out of college or changing to a less challenging major. Objectives: We aimed to determine the effect of a living learning community (LLC) on the retention and success of students seeking entry into a Baccalaureate Science Nursing (BSN) program. Methods: The aim of this descriptive, prospective cohort project was to improve student retention and success by creating a living–learning community (LLC) for first-year students preparing to apply to a BSN program. The effectiveness of this intervention was determined by comparing retention and success for those in the LLC with those who were not in the LLC over a period of 4 years. Results: Fewer students in the LLC dropped out of or failed college (21% vs. 33%), fewer changed majors (24% vs. 27%), and more were ultimately admitted to the BSN program (42% vs. 36%) during their 3rd year of college. Of those not admitted within the study's timeframe, there were more students still preparing to apply to a BSN program than those not in the LLC (13% vs. 3%). Regarding minority outcomes, fewer LLC underrepresented minority (URM) students dropped out of college or failed (29% vs. 43%), but more of them changed majors and remained in college, working towards a college degree in another field of study (43% vs. 29%). There was no apparent effect of participation in the LLC program on minority student nursing program admission success. An equal percentage (29%) of minority students from the LLC group and the non-LLC group were admitted to the BSN program during this study. Conclusions: The limitations affecting this study include the prohibition of large face-to-face gatherings during the initial part of this study and the lingering effects of the pandemic and infection control efforts on student learning outcomes. As reported in prior research, first-year nursing students have a high risk of failing or dropping out of college. However, the students who were able to participate in the LLC demonstrated better student outcomes than those who did not, resulting in more students who were able to move towards their goal of becoming a nurse.